2023
DOI: 10.1177/10742484231185252
|View full text |Cite
|
Sign up to set email alerts
|

Vericiguat reduces electrical and structural remodeling in a rabbit model of atrial fibrillation

Abstract: Purpose: The molecular etiology of atrial fibrillation (AF) and its treatment are poorly understood. AF involves both electrical and structural features. Vericiguat can ameliorate cardiac remodeling in heart failure. The effects of vericiguat on AF, however, are unclear. Here, the actions of vericiguat on atrial structural and electrical remodeling in AF and its possible mechanisms were investigated. Methods and Results: Thirty-six rabbits were randomly allocated to four groups, namely, sham, RAP (pacing with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…Thicker lines indicate stronger correlations. consistent with those of previous studies that have shown that coagulation is increased in the blood of patients with AF [20,21] and that fibrosis is increased in the left atrium of patients with AF [22,23].…”
Section: Discussionsupporting
confidence: 93%
“…Thicker lines indicate stronger correlations. consistent with those of previous studies that have shown that coagulation is increased in the blood of patients with AF [20,21] and that fibrosis is increased in the left atrium of patients with AF [22,23].…”
Section: Discussionsupporting
confidence: 93%
“…The functions of NFAT2, NFAT4 and NFAT1 can overlap with NFAT3, but they might have distinct roles as well. NFAT1 and NFAT4 have been shown to regulate genes related to hypertrophic growth and fibrosis [94] , [95] . NFAT4, in particular, has been associated with the foetal gene program in the heart, which is reactivated during hypertrophy [32] .…”
Section: Discussionmentioning
confidence: 99%
“…Vericiguat, a soluble guanylate cyclase agonist, has been investigated for its potential to treat AF by decreasing electrical and structural remodeling in rabbit models of AF. However, the specific mechanism of its effect on AF remains unclear, and the drug has not yet been widely validated, although it may hold potential value in AF treatment (101). Other studies have indicated that endoplasmic reticulum stress-induced autophagy is a crucial pathway in the progression of AF.…”
Section: Better Symptom Managementmentioning
confidence: 99%